Pengaruh Pelatihan dan Pengembangan Karir terhadap Kinerja Karyawan dengan Digital Well-Being sebagai Variabel Intervening pada PT. Semen Padang (Unit. Departemen SDM) - Revia Rani Safitri; Desi Permata Sari; Chintya Ones Charli (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of Training and Career Development on Employee Performance through Digital Well-being as an intervening variable at PT Semen Padang (HR Department Unit). This study consists of two independent variables, namely Training and Career Development and one dependent, namely Employee Performance and Digital Well-being as the intervening variable. Data collection methods through surveys and distributing questionnaires to employees as respondents using a quantitative approach. The data analysis technique used is Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS) 4.0. The results showed that there is a positive and significant influence between Digital Well-being on Employee Performance at PT Semen Padang (HR Department Unit). There is a positive and significant influence between Training on Digital Well-being at PT Semen Padang (HR Department Unit). There is a positive and insignificant influence between Training on Employee Performance at PT Semen Padang (HR Department Unit). There is a positive and insignificant influence between Career Development on Digital Well-being at PT Semen Padang (HR Department Unit). There is a positive and significant influence between Career Development on Employee Performance at PT Semen Padang (HR Department Unit). Training has a positive effect and is able to mediate between Digital well-being variables on Employee Performance. Career Development has a negative effect and does not mediate between Digital Well-being variables on Employee Performance.